Pengelolaan Pengarsipan Administrasi Desa Berbasis Digital Melalui SDGS Desa di Nagari Tanah Bakali Inderapura - Elimar, Tara; Rimin, Rimin; Samin, Samin (Institut Agama Islam Negeri Kerinci, 2021)
SDGs is a global action plan for the next 15 years, to end poverty, reduce inequality and protect the environment. This activity uses qualitative methods with a case study approach. A case study is a model that focuses on exploration or a particular case that is reviewed in detail and in depth in the form of how and why questions. This activity aims to demonstrate the work program that will be implemented during the KKN period in Nagari Tanah Bakali Inderapura. The researcher entered population data starting from family questionnaires and individual questionnaires into the Village SDGS website assisted by members of the Religious Moderation KKN in Tanah Bakali Inderapura